RNA-Binding Protein IGF2BP1 Associated With Prognosis and Immunotherapy Response in Lung Adenocarcinoma - Liu, JinFeng; Li, Zhi; Cheang, Iokfai; Li, Jinghang; Zhou, Chunlei (Frontiers in Genetics, 2022)
N6-methyladenosine (m6A) is the most common modification in eukaryotic RNAs, and plays a vital role in the tumorigenesis and metastasis of various cancers. However, a comprehensive study of m6A methylation regulators in lung adenocarcinoma (LUAD) is still lacking. The present study aimed to systematically explore the role of m6A methylation regulators in LUAD. RNA sequencing data of 20 m6A methylation regulators and clinical data of LUAD patients were downloaded from the cancer genome atlas (TCGA) database. The prognosis value of m6A methylation regulators in LUAD was evaluated using Gene Expression Profiling Interactive Analysis (GEPIA) and PrognoScan database. The correlation between IGF2BP1 and immune infiltrates in LUAD was investigated via CIBERSORT and Tumor Immune Estimation Resource (TIMER). A total of 15 m6A modification regulators were significantly abnormally expressed in LUAD tissues. Survival analysis revealed that four genes (HNRNPC, HNRNPA2B1, IGF2BP1, IGF2BP3) were significantly associated with poor prognosis in LUAD. Multivariate cox regression analysis showed that only IGF2BP1 was an independent predictor of LUAD after adjusting common clinical parameters.The mutation rates of m6A modification regulators in LUAD were less than 10%. Further analysis revealed that IGF2BP1 expression was significantly correlated with immune infiltration, the expression of immune checkpoints and tumor mutational burden (TMB) in LUAD. Our findings suggest that IGF2BP1 is an independent predictor and related to immunotherapy response in LUAD, which maybe a potential novel biomarker for LUAD prognosis and the status of tumor immunity.